Positive Leadership in Practice : a model for our future - Lucey, Cornelia, 1984-; Burke, Jolanta (New York, NY : Routledge, 2022)
"This book aims to help leaders become the best versions of themselves, achieve extraordinary results and help their team accomplish the same. Packed with research and practical advice from real-life positive leaders, it offers an extensive look into both what high-performance leadership is, and how it can be achieved"--
Includes bibliographical references and index.
Keywords: Leadership -- Psychological aspects; Teams in the workplace -- Management; Organizational effectiveness